2019
DOI: 10.1016/j.adro.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Grade 4 Lymphopenia With Proton Versus Photon Radiation Therapy for Esophageal Cancer

Abstract: PurposeGrade 4 lymphopenia (G4L) during radiation therapy (RT) is associated with higher rates of distant metastasis and decreased overall survival in a number of malignancies, including esophageal cancer (EC). Through a reduction in integral radiation dose, proton RT (PRT) may reduce G4L relative to photon RT (XRT). The purpose of this study was to compare G4L in patients with EC undergoing PRT versus XRT.Methods and materialsPatients receiving curative-intent RT and concurrent chemotherapy for EC were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…Recent years brought renewed interest in the immuno-modulatory effects of RT, including AE [15], and the depletion of lymphocytes [1624], both highlighting the importance of the anti-tumor immune system function. Radiation, by itself, can lead to increased antigen shedding and presentation of neo-antigens from the tumors leading to maturation and activation of antigen presenting cells (APCs), increased immuno-stimulatory cytokine production, increased CD-8 T cell and APC infiltration, and improved acquisition of immune stimulatory phenotype [37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years brought renewed interest in the immuno-modulatory effects of RT, including AE [15], and the depletion of lymphocytes [1624], both highlighting the importance of the anti-tumor immune system function. Radiation, by itself, can lead to increased antigen shedding and presentation of neo-antigens from the tumors leading to maturation and activation of antigen presenting cells (APCs), increased immuno-stimulatory cytokine production, increased CD-8 T cell and APC infiltration, and improved acquisition of immune stimulatory phenotype [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The real value of the immunomodulatory effects of RT have yet to be defined. The potential beneficial immune stimulating properties of RT have been questioned by many scientists in the past and present, with a renewed focus on the immune-mediated abscopal effects (AE) [14] as well as on the depletion of lymphocytes [15, 16]. Recent studies have described an association between the RT-induced lymphopenia with poor oncologic outcome, with the thought that RT using larger volumes/multiple daily fractions can lead to global immunosuppression [1720].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data show that the conventional radiotherapy predominantly generates immune-suppressive effects [ 9 ]. Furthermore, it has been shown that irradiation of larger volumes in multiple daily fractions correlates with radiation-induced lymphopenia [ 10 , 11 ], leading to a global immunosuppression and consequent poor oncologic outcome [ 12 , 13 ]. These radiation-mediated immune-suppressive effects may negatively affect the therapeutic efficacy in many tumor types [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation alone can induce volume-dependent lymphopenia via irradiation of lymphoid organs, bone marrow, and circulating lymphocytes (40). Radiation modality may also contribute to lymphopenia, as esophageal cancer patients treated with photons experienced more Grade 4 lymphopenia compared to those treated with protons, suggesting a dependence on total integral dose to lymphocyte-containing normal structures such as the vasculature (41). Lymphocytes are very radiosensitive, susceptible to apoptosis in response to doses as low as 1–2 Gy, with evidence indicating that activated T cells may be more radio-resistant (31, 32, 42).…”
Section: Discussionmentioning
confidence: 99%